Original paperA simple technique for the generation of institution-specific nomograms for permanent prostate cancer brachytherapy - Lafata, Kyle J.; Bushe, Harry; Aronowitz, Jesse N. (Journal of Contemporary Brachytherapy, 2014)
Purpose: Nomograms once had a vital role in prostate brachytherapy practice. Although some of their functions have been assumed by computerized dosimetry, many programs still find them useful to determine the number and strength of seeds to be ordered in advance of the implant. As it has been demonstrated that brachytherapists differ in their implant practices and preferences (in regard to seed distribution and total implanted activity), we propose a simple technique for generating institution-specific nomograms. Material and methods : Using the data generated by previous implants, we demonstrate a simple technique, utilizing ubiquitous software, for generating nomograms to predict seed number, strength, and total implant activity. Results: Despite wide variations in the degree of post-implant swelling (+12% to +56%), nine of the first ten implants using the generated nomogram have met all target dose parameters. Conclusions: It is appropriate for each institution to develop nomograms specific to their prostate brachytherapy technique and constraints. Nomograms can estimate the number and strength of seeds to be ordered, and may partially compensate for the effects of implant-induced swelling.